Complete Genome of Lactobacillus iners KY Using Flongle Provides Insight Into the Genetic Background of Optimal Adaption to Vaginal Econiche - Kwak, Woori; Han, Young-Hyun; Seol, Donghyeok; Kim, Hyaekang; Ahn, Hyeonju; Jeong, Misun; Kang, Jaeku; Kim, Heebal; Kim, Tae Hyun (Frontiers in Microbiology, 2020)
Despite the importance of Lactobacillus iners and its specific characteristics for the study of vaginal adaption, its genome and genomic researches for identifying molecular backgrounds of these specific phenotypes are still limited. In this study, the first complete genome of L. iners was constructed using cost-effective sequencing platform called Flongle from Oxford Nanopore and comparative genome analysis was conducted using a total 1,046 strain genomes from 10 vaginal Lactobacillus species. Single-molecule sequencing using Flongle effectively reduced the limitation of 2nd generation sequencing in GC biased genomic region and comparative genome analysis identified 3 potential core genes (INY, ZnuA, and hsdR) related to the specific phenotype of L. iners for vaginal adaption. In addition, prophage analysis for 1,046 strain genomes to identify the species specificity. The number of prophages in L. iners and L. helveticus genomes was significantly smaller than other vaginal Lactobacillus species and Type I R/M system related to one of the specific core genes (hsdR) was suggested as the reason of reduced bacteriophage invasion. The first complete genome of L. iners and 3 specific genes identified in this study will be useful resources to further expand our knowledge of vaginal Lactobacillus and its specific adaption.